Esquisses Accomplies. (Paris : Galerie Darbonne-Roy, 1983)
Arsic, Paul ; Bontoux, Jean-Martin ; Bron, Michel ; Cat, Roland ; Férreira ; Foulc, Thieri ; Huss, Judson ; Henricot ; Kiras, Jean ; Lacombe, Pierre ; Pardo, Frédéric ; Rimbault, Gilles ; Rubel, Georges ; Verlinde
Esquisses Accomplies, Galerie Darbonne-Roy, Paris, du 11 mai au 30 juillet 1983
boek